Public Policy Network and Employee Performance: Exploring the Relationship Between Organizational Culture and Education at the Probolinggo Regency Regional Inspectorate - Wicaksono, Pamungkas; Rulinawaty; Mufti, Muslim (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2025)
This study aims to analyze the relationship between organizational culture, education and training, as well as public policy networks as intervening variables on employee performance in the Probolinggo Regency Regional Inspectorate. This study uses a quantitative approach with the SmartPLS-based Structural Equation Modeling (SEM) method. Data was collected through a questionnaire distributed to 59 employees at the Probolinggo Regency Regional Inspectorate. The results of the study show that organizational culture has a positive and significant influence on public policy networks and employee performance. The public policy network also has a positive effect on employee performance. Education and training have been shown to have a positive influence on employee performance, although they do not show a significant influence on public policy networks. In addition, organizational culture has an indirect effect on employee performance through public policy networks, while education and training do not show a significant mediating influence on employee performance. The findings of this study are expected to contribute to better policy making within the Probolinggo Regency Regional Inspectorate and enrich the literature on the influence of organizational culture, education, and public policy on the performance of employees in the government sector.